FROM DIGITAL-EXPOSURE TO PURCHASE-INTENTION: MODELING CONSUMER RESPONSES THROUGH AFFECTIVE, COGNITIVE, AND BEHAVIORAL MECHANISMS - Achmad Yanu Alif Fianto; Slamet Riyadi; Rudi Santoso (Majalah Ekonomi, 2026)
The rapid expansion of digital marketing has fundamentally transformed the ways in which consumers interact with brands and make purchasing decisions. Understanding the psychological mechanisms that connect digital marketing stimuli with consumer behavior has therefore become increasingly important. This study investigates how the digital marketing environment and brand communication strategy influence purchase intention through affective, cognitive, and behavioral consumer responses. Drawing upon the Stimulus–Organism–Response (S-O-R) framework, this research proposes an integrated model explaining how marketing stimuli shape consumer decision-making processes in digital contexts. A quantitative research design was employed using survey data collected from digital consumers in East Java, Indonesia who actively interact with marketing content on social media and online platforms. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among the constructs. The results reveal that both digital marketing environment and brand communication strategy significantly influence affective response, cognitive evaluation, and behavioral engagement. Furthermore, these consumer responses positively affect purchase intention, indicating that emotional experiences, rational evaluations, and active engagement jointly shape consumer purchasing decisions. The findings contribute to digital marketing literature by empirically validating the affective–cognitive–behavioral mechanism within an integrated marketing stimulus framework in an emerging market context. The study also provides practical insights for marketers seeking to design more effective digital marketing strategies that foster consumer engagement and strengthen purchase intentions.